Carta de Santiago Veve a Roberto H. Todd - Veve, Santiago; Todd, Roberto H. (My University, 1928)
Carta relacionada a gestiones de Gerardo Forrest en Puerto Rico para la Guerra de Independencia hacia 1897.
Keywords: Forrest, Gerardo; García, Margarita; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.; Veve, Santiago--Correspondencia.; Veve, Santiago--Correspondence.; Camuñas, Manuel; Venegas, Luis